Pelatihan Tata Kelola Administrasi Tax Center Politeknik Negeri Jember - Oryza Ardhiarisca; Rahma Rina Wijayanti; Nur Faizin (Journal of Community Development, 2024)
Administration is a source that can be used to obtain data or information. The Jember State Polytechnic Tax Center should carry out administration well in order to provide the best service. One of the administrations that must be carried out by the Polije Tax Center is to administer customer data that is present at the Tax Center. Providing services to customers can take the form of consultations on filling out Annual Tax Returns (SPT) and tax consultations. Information on the number of customers can be an indicator of tax compliance, especially for Jember State Polytechnic employees. Apart from that, this activity also provided a book for recording incoming and outgoing letters so that they could archive letters at the Tax Center. The method used is surveys, discussions and also training for tax volunteers. The result of this service activity is that tax volunteers achieve understanding regarding the importance of administrative governance and administrative management. The achievement of service activities is demonstrated by the results of feedback from tax volunteers at the Tax Center. The feedback results show that 81% respondent stated that this service activity is very beneficial for partners